Keabsahan Putusan Badan Arbitrase Syariah Nasional Dalam Penyelesaian Sengketa Ekonomi Syariah Di Indonesia - Eko Priadi; Mhd Erwin Munthe (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2019)
The growth of Sharia Economic accelerating in the last three decades is also affecting the increase of potential disputes on sharia economic field. For the purposes of fast, effective and efficient dispute settlement, the disputing parties tend to prefer non-litigation dispute settlement through alternative dispute resolutions (ADR), one of which is through the National Sharia Arbitration Board. The results of this study showed that the authority of the National Sharia Arbitration Board on sharia economic dispute settlement is determined by whether or not the arbitration agreement, either before a dispute arises (Pactum Compromittendo) or after the dispute arises (Acta Compromise). Thereby, the legitimacy of the authority of the National Sharia Arbitration Board on Syariah economic dispute settlement, based on the principle of Pacta Sunt Servanda and Consensual Principles contained in the Civil Code. Further, registration and execution of the National Sharia Arbitration Board verdict should be carried out by the Religious Courts, including the cancellation of the legal action on the verdict. It is based on two factors: (1) the basic legality of absolute competence of the Religious Courts in the Islamic economic dispute resolution as set out in Article 49 of Regulation No. 3/2006 on the Religious Courts; and (2) the basic relevance of the substance of Islamic law which is implemented by the National Sharia Arbitration Board.